Konsep Samsara dalam Agama Budha dan Hindu - Wahid, Annisa; S. Taruna, Doddy; Taufiq Rahman, Mohamad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
This study aims to explore the concept of samsara in Buddhism and Hinduism by focusing on three aspects: (1) the existence of samsara in both religions, (2) the influence of samsara on their respective doctrinal and philosophical frameworks, and (3) a comparison between the interpretations of samsara in Buddhism and Hinduism. The research method used is qualitative, with a literature-based approach. The results indicate that although samsara appears in both traditions with similar functions as a cycle of rebirth and suffering caused by karma, the final interpretations differ. In Hinduism, samsara is viewed as a form of punishment from past lives, which continues through repeated births until one’s sins are cleansed this process is closely related to the doctrine of punarbhava (reincarnation), and forms one of the five core beliefs (panca sraddha). In contrast, Buddhism interprets samsara not as divine punishment, but as a state of suffering rooted in ignorance and desire. It is classified into six realms of existence three lower (hell beings, hungry ghosts, animals) and three higher (humans, demigods, gods). These distinctions reflect the doctrinal emphasis each religion places on the nature of existence and liberation.